EKSISTENSI KELOMPOK MUSIK GAMAT MANDAYU SANGGAR SENI PELANGI RANAH MINANG DI KOTA PADANG - Jimmy Ferdian; Wimbrayardi Wimbrayardi; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to find out and describe the existence of the Gamat Mandayu Musik group Pelangi Ranah Minang Art Studio in Padang City, seen from users and functions. This research is a qualitative research with descriptive analysis method. The results showed that the gamat mandayu music group still existed with limited training grounds and lack of government attention. Lack of public attention and government increasingly eliminate the existence of gamad music in the city of Padang. For that, gamad music in Padang City still exists, the role of the City government is needed to maintain this cultural heritage. The functions found in gamat music arts are: (1) emotional disclosure function, (2) aesthetic comprehension function, (3) entertainment function, (4) communication function, (5) physical reaction function. Keywords: Existence, Gamat Mandayu, Pelangi Ranah Minang Art Studio